2019
DOI: 10.1007/s10551-019-04179-8
|View full text |Cite
|
Sign up to set email alerts
|

Labour Force Participation and Employment of Humanitarian Migrants: Evidence from the Building a New Life in Australia Longitudinal Data

Abstract: This study uses the longitudinal data from the Building a New Life in Australia survey to examine the relationships between human capital and labour market participation and employment status among recently arrived/approved humanitarian migrants. It includes attention to the heterogeneity of labour force participation and employment status across genders and also migration pathways. We find that the likelihood of participating in the labour force is higher for those who had preimmigration paid job experience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 92 publications
(68 reference statements)
1
20
0
Order By: Relevance
“…(Re)gaining lost resources and acquiring new skills relevant to the host society has been found crucial in securing employment (Hobfoll, 2001;Ryan et al, 2008). As shown in previous studies, newcomers' labor market positions can be explained through a wide range of such resources (for an overview, see Heath and Cheung, 2007;Ott, 2013), including pre-and post-migration cultural capital (Waxman, 2001;Chiswick and Miller, 2009;Hartog and Zorlu, 2009;Kanas and van Tubergen, 2009;de Vroome and van Tubergen, 2010;Correa-Velez et al, 2013;Cheng et al, 2019), social capital (Waxman, 2001;de Vroome and van Tubergen, 2010;Kanas et al, 2011;Correa-Velez et al, 2013;Cheung and Phillimore, 2014) and personal capital (Phillimore, 2011;Walther et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…(Re)gaining lost resources and acquiring new skills relevant to the host society has been found crucial in securing employment (Hobfoll, 2001;Ryan et al, 2008). As shown in previous studies, newcomers' labor market positions can be explained through a wide range of such resources (for an overview, see Heath and Cheung, 2007;Ott, 2013), including pre-and post-migration cultural capital (Waxman, 2001;Chiswick and Miller, 2009;Hartog and Zorlu, 2009;Kanas and van Tubergen, 2009;de Vroome and van Tubergen, 2010;Correa-Velez et al, 2013;Cheng et al, 2019), social capital (Waxman, 2001;de Vroome and van Tubergen, 2010;Kanas et al, 2011;Correa-Velez et al, 2013;Cheung and Phillimore, 2014) and personal capital (Phillimore, 2011;Walther et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…They did however not find an impact of English language proficiency. Also in Australia, Cheng et al (2019) indicated the impact of pre-immigration paid job experience, completed study/job training, having job searching knowledge/skills in Australia, possessing higher proficiency in spoken English and mental health. Touching upon the role of (labor market) policies, Kanas and Steinmetz (2021) establish the significant role of such policies in the economic disadvantage of family migrants and refugees.…”
Section: Theoretical Considerations (Re)gaining Resources and Labor M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the now extensive research literature on the position of refugees generally focuses on just one outcome indicator. A good deal of research has for example been carried out on the labour market position of refugees (de Vroome and van Tubergen, 2010;Ott, 2013;Gathmann, 2014;Bakker, 2016) and the determinants of the command of the host country language (Waxman, 2001;Kanas and van Tubergen, 2009;Khoo, 2010;de Vroome and van Tubergen, 2010;Cheng et al, 2019). Much less attention has been given to the extent to which refugees combine certain forms of participation.…”
Section: Introductionmentioning
confidence: 99%